Magnitude of tuberculosis treatment outcomes and associated factors in public health institutions of Arba Minch town, Southern Ethiopia: A multi-centered retrospective cross-sectional study - Behailu Asmamaw; Temesgen Tamiru Tadese; Rediet Yifru Mamo; Berhanu Amare Taye; Abrham Workineh Azale; Yohannes Chemere Wondmeneh; Dagmawi Nega Shibeshi; Eunice Borkor Bortequaye; Temesgen Teklu Ziza; Temesgen Esayas Bolliso; Tiwabwork Tekalign; Awoke Guadie (PLoS ONE, 2025)
Background In Ethiopia, the incidence rate of tuberculosis (TB) has been steadily increasing, from 119 per 100,000 in 2021–126 per 100,000 in 2022 and 146 per 100,000 in 2023. Moreover, TB remains the second leading cause of death after malaria, and the third leading cause of hospital admissions. So, the aim of this study is to determine the treatment outcome and associated factors in the public health institutions of Arba Minch town. Methods A multi-centered retrospective cross-sectional study was conducted involving 609 tuberculosis patients admitted from September 2021-August 2024 at public health institutions in Arba Minch town. A structured data extraction form was used by trained research assistants to collect the data from TB patient registration record books. Variables with a p-value <0.25 in binary logistic regression were further analyzed using multivariable logistic regression. Statistically significant factors were considered those with a p-value <0.05. Result The majority (53.7%) of the participants were aged between 21 and 40 years. Most participants were diagnosed with pulmonary tuberculosis (71.8%) and found to be new (92.9%) patients. According to this study, the magnitude of successful treatment outcomes was found to be 86.9%. In the multivariate logistic regression, being unmarried (p = 0.023), educational level (p = 0.028), and having extra-pulmonary TB (p = 0.017) have been found significantly associated with successful treatment outcome. Conclusion The study indicates a relatively positive rate of successful treatment outcomes for TB. Although the treatment outcome results are positive, targeted interventions are needed for individuals who are married, have a low educational status, and have been diagnosed with pulmonary tuberculosis.